2014
DOI: 10.1002/jbm.a.35371
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone/starch composite: Fabrication, structure, properties, and applications

Abstract: Interests in the use of biodegradable polymers as biomaterials have grown. Among the different polymeric composites currently available, the blend of starch and polycaprolactone (PCL) has received the most attention since the 1980s. Novamont is the first company that manufactured a PCL/starch (SPCL) composite under the trademark Mater-Bi®. The properties of PCL (a synthetic, hydrophobic, flexible, expensive polymer with a low degradation rate) and starch (a natural, hydrophilic, stiff, abundant polymer with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 199 publications
(262 reference statements)
0
48
0
1
Order By: Relevance
“…The polymer/solvent miscibility has been shown to have a direct bearing on the final fiber diameter and morphology. For instance, fibers made from PLA in dichloromethane have been shown to have a broader range of fiber diameters [32][33][34]. Results reported by Wei et al [35] on the electrospinning of Polyvinylidene fluoride (PVdF) nanofibers showed that the concentrations of solvent Methyl ethyl ketone (MEK) in DMF greatly influenced the dimensions and morphology of PVdF nanofibers.…”
Section: Introductionmentioning
confidence: 92%
“…The polymer/solvent miscibility has been shown to have a direct bearing on the final fiber diameter and morphology. For instance, fibers made from PLA in dichloromethane have been shown to have a broader range of fiber diameters [32][33][34]. Results reported by Wei et al [35] on the electrospinning of Polyvinylidene fluoride (PVdF) nanofibers showed that the concentrations of solvent Methyl ethyl ketone (MEK) in DMF greatly influenced the dimensions and morphology of PVdF nanofibers.…”
Section: Introductionmentioning
confidence: 92%
“…The most studied synthetic polymers in bone tissue regeneration are aliphatic polyesters like poly(lactic acid) (PLA), poly(ε‐caprolactone) and poly(glycolic acid), as well as their copolymers and derivatives. These polymers are degraded by hydrolysis in vivo and have the advantage of being easily tailored in different shapes, according to the mechanical demands in the particular bone treated (Yan et al., ; Ali Akbari Ghavimi, Ebrahimzadeh, Solati‐Hashjin, & Abu Osman, ; Pilipchuk et al., ). However, synthetic polymers still show some concerns about osteoconductivity, absorption timing and local pH alterations.…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…Therefore, PCL has been blended with other polymers (i.e., starch, PLA, etc.) to reduce costs while preserving or improving the biodegradability of the resulting materials …”
Section: Biodegradable Polymersmentioning
confidence: 99%